LED Lighting Technology Localization: Technological Innovation in the United States - Donghong Chen (Innovation in Science and Technology, 2025)
With the rapid development of the global LED lighting market, the United States, as one of the important consumer markets, has attracted the attention of many enterprises. 360 LED LLC, an LED lighting enterprise established in China, has actively carried out technological innovation and cooperation by setting up subsidiaries in the United States, promoting the localization of LED lighting technology. This paper deeply investigates the technological innovation practices of 360 LED LLC in the United States, including specific measures and achievements in product development, team building, and process improvement. It also explores the cooperation models between 360 LED LLC and local suppliers, research institutions, universities, and sales channels in the United States, analyzing how these collaborations have facilitated product localization and technology transfer. The study finds that through technological innovation and cooperation, 360 LED LLC has not only met the special needs of the US market and improved product compatibility and user experience but also successfully expanded its market share and enhanced brand awareness.